2010
DOI: 10.1074/jbc.m110.167668
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Homoserine Lactone Activates Store-operated cAMP and Cystic Fibrosis Transmembrane Regulator-dependent Cl− Secretion by Human Airway Epithelia

Abstract: The ubiquitous bacterium Pseudomonas aeruginosa frequently causes hospital-acquired infections. P. aeruginosa also infects the lungs of cystic fibrosis (CF) patients and secretes N-(3-oxo-dodecanoyl)-S-homoserine lactone (3O-C12) to regulate bacterial gene expression critical for P. aeruginosa persistence. In addition to its effects as a quorum-sensing gene regulator in P. aeruginosa, 3O-C12 elicits cross-kingdom effects on host cell signaling leading to both pro-or anti-inflammatory effects. We find that in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 50 publications
5
39
0
Order By: Relevance
“…Furthermore, BUYCK et al [35] have shown that P. aeruginosa LPS-stimulated Cl − currents through CFTR channels in 16HBE14o-cells, probably via a calcium signal. Similarly, N-(3-oxo-dodecanoyl)-S-homoserine lactone (3O-C12), a quorum sensing molecule secreted by P. aeruginosa, has been shown to rapidly enhance Cl − and fluid secretion as well as cytosolic calcium and cAMP levels [36]. It has also been reported that P. aeruginosa flagellin activated CFTR-dependent anion secretion in Calu-3 (through p38 signalling) as well as in primary cultures of human bronchial epithelial cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BUYCK et al [35] have shown that P. aeruginosa LPS-stimulated Cl − currents through CFTR channels in 16HBE14o-cells, probably via a calcium signal. Similarly, N-(3-oxo-dodecanoyl)-S-homoserine lactone (3O-C12), a quorum sensing molecule secreted by P. aeruginosa, has been shown to rapidly enhance Cl − and fluid secretion as well as cytosolic calcium and cAMP levels [36]. It has also been reported that P. aeruginosa flagellin activated CFTR-dependent anion secretion in Calu-3 (through p38 signalling) as well as in primary cultures of human bronchial epithelial cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the presence of Tg ϩ C12, Ca er is low but Ca mito (Fig. 8) and Ca cyto (30) are higher than control, and C12-triggered apoptosis is blocked. Because Ca 2ϩ -free solution and/or Ca 2ϩ -free solution ϩ BAPTA-AM were inhibitory to C12-induced degradation of barrier function and activation of caspase 3/7, it seems unlikely that C12 activated apoptosis by increasing Ca cyto or that the antiapoptotic effects of Tg were mediated through an increase in Ca cyto .…”
Section: C852 Thapsigargin Prevents C12-induced Apoptosismentioning
confidence: 81%
“…The data are consistent with the idea that C12 has multiple, yet selective, effects on airway epithelial cells (e.g., C6 and C4 homoserine lactone have no effect on caspase 3/7 of airway epithelia). The inositol 1,4,5-trisphosphate receptor is activated, and Ca 2ϩ is released from the ER; Ca mito decreases, and mitochondria depolarize and release cytochrome c; proteins and oxidizing contents are released from the ER into the cytosol; nuclei shrink and fragment; and tight junctions degrade, and barrier function is lost (27,30, present data). Tg pretreatment inhibits most of these proapoptotic effects.…”
Section: C852 Thapsigargin Prevents C12-induced Apoptosismentioning
confidence: 95%
See 2 more Smart Citations